2019
DOI: 10.1016/j.adro.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies and clinical outcomes of locally advanced pancreatic cancer patients treated at high-volume facilities and academic centers

Abstract: Purpose Locally advanced pancreatic cancer (LAPC) treatment has varying practice patterns with poor outcomes. We investigated treatment using single-agent chemotherapy and multiagent chemotherapy (MAC) with or without radiation therapy (RT) at high-volume facilities (HVFs) and academic centers (ACs). Methods and Materials The National Cancer Database was used to obtain data on 10,139 patients with LAPC. HVF was defined as the top 5% of facilities per number of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Though the literature reveals select studies implicating female sex in the epidemiology of PDAC [35] , [36] , there is no proven association of female sex with disease outcomes, and the result herein should be considered hypothesis-generating. Several prior reports, however, have shown an association of improved outcomes for patients managed with PDAC treated at academic or high volumes centers [37] , [38] consistent with the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Though the literature reveals select studies implicating female sex in the epidemiology of PDAC [35] , [36] , there is no proven association of female sex with disease outcomes, and the result herein should be considered hypothesis-generating. Several prior reports, however, have shown an association of improved outcomes for patients managed with PDAC treated at academic or high volumes centers [37] , [38] consistent with the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Further description of the characteristics of studies included is shown in Table 1 and the Supporting Information (Tables S2-S4). [15][16][17][18][19][20][21][22][23][24][25][26][27][28]38, The network included a total of 14,065 patients of whom 1772 (13%), 11,073 (79%), and 1220 (9%) were in the LA-BR, LA-UR, and UFR groups, respectively (Table S4). The network consisted of eight unique treatment subgroups and 57 pairwise comparisons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An additional post-hoc sensitivity analysis was performed to evaluate the effect of excluding a large cohort from the National Cancer Database, which may have resulted in data duplication. 38 Prespecified sources of heterogeneity were defined in the study protocol, and subgroup analyses and meta-regression were used to explore suspected sources of heterogeneity. 39 All statistical analyses were performed using R (version 3.6.1 Action of the Toes) in RStudio (version 1.1.419).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, prior studies have demonstrated differences in care for PDAC patients treated at high volume and academic centers, including evidence of closer adherence to national guidelines at these centers. 36,37 A notable limitation to the current study is that the type and duration of chemotherapy administered (including if all planned therapy was completed) cannot be ascertained from the database. In addition, results of both the ESPAC-4 5 and PRODIGE-24 7 trials have been published subsequent to the treatment of patients included in the current analysis.…”
Section: Hpbmentioning
confidence: 99%